Food consumption pattern in cervical carcinoma patients and controls - Labani, Lakshmi; Andallu, B; Meera, M; Asthana, S; Satyanarayana, L (Indian Journal of Medical and Paediatric Oncology, 2009)
Background:The uterine cervix is the second most common site of cancer among Indian women.Though the human papillomavirus has been demonstrated to be a causative agent for this cancer, a variety of other risk factors are in play, such as sexual and reproductive patterns, socioeconomic, hygienic practices, and diet. The accumulated evidence suggests that cervical cancer is preventable and is highly suitable for primary prevention. The dietary intake of antioxidants and vitamins like vitamin A, carotenoids, vitamin C, folacin and tocopherol is found to have protective effects against cancer of the cervix. Dietary data regarding cervical cancer are still scanty.Objective:The present study was therefore undertaken to study the dietary pattern among uterine cervical cancer patients and normal controls.Materials and Methods:A total of 60 consecutive patients and 60 controls were enrolled from a referral hospital during the year 2004. A schedule inclusive of the food frequency pattern and 24-h dietary recall along with the general information was administered to all the enrolled subjects to describe findings on the food consumption pattern along with other important factors.Results:The mean intake of energy, protein, vitamins, etc., between the cases and controls was not significantly different except for the vitamin C level. Serum vitamin E was found to have lower average in patients as compared to controls. The nutrient intake of cervical cancer patients and controls was grossly deficient in the socioeconomic group studied. With regard to the macronutrient intake, calorie and protein intakes showed a deficit of around 50% when compared to RDA.Conclusion:The food consumption profile was not significantly different between cervical cancer patients and normal controls.
Keywords: Cervical cancer; food consumption; low socioeconomic women